IMPACT ON ROADSIDE SOIL QUALITY DUE TO DEPOSITION OF VEHICLE RELATED CONTAMINANT (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Aim: The study aimed to evaluate the impact of vehicle-related contaminants on roadside soil quality by analyzing seasonal variations in pH levels, electric conductance (EC), and metal concentrations (Lead and Cadmium) across different site types, including roadside, residential, agricultural, and control areas in Sri Ganganagar.Material and Methods: Soil samples were collected from selected sites over three years (2019–2021) using a standardized sampling method. Samples were analyzed for pH, EC, Lead (Pb), and Cadmium (Cd) using Atomic Absorption Spectroscopy (AAS) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) after acid digestion. Data analysis was performed using SPSS version 25.0, applying statistical tools such as mean differences, Standard Deviation (SD), Standard Error Deviation (SED), and t-ratio to compare seasonal variations.Results: The findings revealed significant seasonal variations in soil parameters. pH levels decreased notably in roadside and residential areas from winter to summer. Electric Conductance (EC) increased significantly during summer across most site types. Lead (Pb) and Cadmium (Cd) concentrations showed substantial seasonal increases, with roadside and residential areas exhibiting the highest contamination levels.Conclusion: The study demonstrated that seasonal dynamics significantly influence soil quality parameters in areas affected by vehicle emissions. The observed variations emphasize the necessity for targeted soil management strategies to mitigate environmental risks arising from heavy metal accumulation.